Growth and Biomass Production of Different Eucalyptus Species on Riverine Soils of Punjab - Singh, Harmandeep; Garg, Rakesh K.; Chauhan, Sanjeev K.; Sharma, Sandeep (Indian Forester, 2019)
A field experiment was conducted at University Seed Farm of Punjab Agricultural UniversityÂ A field experiment was conducted at University Seed Farm of Punjab Agricultural University Ladhowal, Ludhiana to investigate the growth and biomass of different Eucalyptus species on riverine soils of Punjab. Five different species of Eucalyptus were compared for the growth and biomass production, and changes in soil physico-chemical properties after one year of harvesting of trees under riverine soils of Punjab were also assessed. Different morphological parameters for tree growth viz. tree height, girth at collar level, GBH, canopy spread and tree biomass viz. fresh stem weight, fresh branch weight, fresh leaf weight and bark biomass were recorded. Soil pH, EC, soil organic carbon, bulk density, available N, P and K were also estimated. Tree growth and biomass was maximum in Eucalyptus 288 clone as compared to other four Eucalyptus species. Soil physico-chemical properties were better under tree plantation. Organic matter in the form of litter fall at the time of harvesting was more as compared to those observed one year after harvesting of plantation. Soil pH, electric conductivity, soil organic carbon, available nitrogen, phosphorus and potassium decreased after one year of harvesting in all species studied.